1-Aminocyclopropane 1-Carboxylic Acid and Its Emerging Role as an Ethylene-Independent Growth Regulator - Polko, Joanna K.; Kieber, Joseph J. (Frontiers in Plant Science, 2019)
1-aminocyclopropane 1-carboxylic acid (ACC) is the direct precursor of the plant hormone ethylene. ACC is synthesized from S-adenosyl-L-methionine (SAM) by ACC synthases (ACS) and subsequently oxidized to ethylene by ACC oxidases (ACO). Exogenous ACC application has been used as a proxy for ethylene in numerous studies as it is readily converted by nearly all plant tissues to ethylene. However, in recent years, a growing body of evidence suggests that ACC plays a signaling role independent of the biosynthesis. In this review, we briefly summarize our current knowledge of ACC as an ethylene precursor, present new findings with regards to the post-translational modifications of ACS proteins and to ACC transport. We also summarize the role of ACC in regulating plant development, its involvement in cell wall signaling, guard mother cell division, and pathogen virulence.